Pemanfaatan Hutan Mangrove Untuk Peningkatan Pendapatan Nelayan - Ismon Zakya HS; Heryudarini Harahap; Rudianda Sulaeman (Badań Perencanaan Pembangunan Dearth, Penelitian dań Pengembangan Provinsi Riau, 2017)
Mangrove ecosystem has important function which can support human life either directly or indirectly, that is ecological function of mangrove ecosystem to guarantee the maintenance of physical environment, and social and economic function. The aim of this study is to calculate the income of fishermen through mina mangrove business through the enlargement of mangrove crab (Scylla serrata). The method is experiment. Crab enlargementwas carried out with high and low density mangroves confinement for one month. The success of crab enlargement was rated by weight gain, feed efficiency and crab survival rate. Investment feasibility analysis is with Net Benefit Cost Ratio (B/C). The place of research is in Indragiri Hilir District. The results showed that mangrove crabs maintained in high density mangroves have increased weight, feed efficiency and better survival rate than mangrove crabs kept in low density mangrove confinement. The gross revenue obtained in high-density confinement was Rp. 318.257 whereas in low-density confinement only Rp. 181.603. Value R/C ratio or ratio between gross receipts with cost for high density reaches 1.68, while for low density was only 1.05. Payback period for both types of confinement were underone month. Net value Benefit Cost Ratio for high density reached 6.35 while low density was only 2.84.